2023
DOI: 10.1029/2022ea002811
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Formation Mechanism of the Cloud Vertical Structure Over the Southeastern Tibetan Plateau in Summer

Abstract: Cloud significantly impacts the Earth's radiation budget and is also a major source of uncertainty in global climate modeling (Bony et al., 2015;Ramanathan et al., 1989;Zhang et al., 2022). Cloud vertical structure (CVS), characterized by cloud top height (CTH), cloud base height (CBH), cloud thickness and the vertical distribution of multi-layer clouds, significantly impacts the atmospheric circulation by changing the net radiation budget and the energy redistribution at the top of the atmosphere (AT) (Chen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Ma et al. (2023) indicated that single‐layer cloud formation over the TP is closely tied to water vapor enhancement and significantly increases at 400 hPa, while two‐ and three‐layer clouds are associated with stronger South Asian High and vertical wind shear at 200 hPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al. (2023) indicated that single‐layer cloud formation over the TP is closely tied to water vapor enhancement and significantly increases at 400 hPa, while two‐ and three‐layer clouds are associated with stronger South Asian High and vertical wind shear at 200 hPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Unsurprisingly, because of high topography of the TP, clouds with base heights above 6.5 km or cloud bases below 6.5 km but half (or more) of the cloud body above 6.5 km were prevalent (e.g., h, Hxh and hxM). Ma et al (2023) indicated that single-layer cloud formation over the TP is closely tied to water vapor enhancement and significantly increases at 400 hPa, while two-and three-layer clouds are associated with stronger South Asian High and vertical wind shear at 200 hPa, respectively. Regardless of the cloud fraction weights of different CVDs, almost all CVD categories generate strong negative shortwave CRE (exceeding 150 Wm 2 ), except H-type (only 26.14 Wm 2 ), and those with lower cloud base tend to exert stronger cooling effect (exceeding 200 Wm 2 ), especially for HxhxM (deep convective clouds, up to 458.94 Wm 2 ).…”
Section: Radiation Precipitation and Heating Rate Characteristics Of ...mentioning
confidence: 99%